FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI MAHASISWA TINGKAT AKHIR PRODI KESEHATAN MASYARAKAT UNIVERSITAS HANG TUAH PEKANBARU - Anisa, Nirma; Septiani, Winda; Raviola, Raviola (Ensiklopedia of Journal, 2024)
Lifestyle and nutritional intake are factors that affect the nutritional status of final year students. Undernutrition conditions in adulthood due to lack of energy cause students to get tired easily because of the many demands ranging from thesis work, organizational duties and personal problems they experience and several other factors. This study aims to determine the factors associated with the nutritional status of final year students of the Hang Tuah University Pekanbaru public health program. By using quantitative research methods with observational analytic research type, the design used is cross sectional with consecutive sampling technique. With a population of 203 people with a sample size of 67 respondents. This research was conducted from July to August 2023. Data collection tools using questionnaires with interview methods. Data analysis used is univariate and bivariate using the chi square test. From the results of the study obtained factors associated with nutritional status, namely Stress (p value = 0.000), Emotional Eating (p value = 0.48), Energy Intake (p value = 0.003), Sleep Qualities (p value = 0.32). It is recommended for students to pay more attention to lifestyle and nutritional intake so that nutritional status remains normal and body health is well maintained. Keywords : Energi intake, Nutrition, Hang Tuah, Student, Stress